A 15 year record of frontal glacier ablation rates estimated from seismic data. Issue 23 (15th December 2016) - Köhler, Andreas; Nuth, Christopher; Kohler, Jack; Berthier, Etienne; Weidle, Christian; Schweitzer, Johannes
Abstract: We present a unique time series of continuous glacier frontal ablation rates with weekly resolution over 15 years estimated from seismic calving observations at Kronebreen, Svalbard. Using linear statistical models, we calibrate the seismic record with 7 years of satellite‐derived frontal ablation measurements. The two basic input parameters required for our models are the cumulative duration of individual seismic calving events and the incompleteness of the seismic record to correct for the effect of seismic background noise. Frontal ablation follows the seasonal glacier speedup, peaking 1–2 months after the melt season maximum. Short‐lived peaks are associated with melt and rain events. Cumulative frontal ablation of Kronebreen between 2001 and 2015 is about 4.0 km 3  (3.7 Gt), with the greatest annual loss (0.45 km 3 ) between 2013 and 2014 at the onset of the recent accelerated retreat of the glacier. Our approach provides a potential method for monitoring tidewater glaciers worldwide that have sufficiently close seismic instrumentation. Key Points: Seven years of satellite‐derived glacier frontal ablation are used to develop models that estimate weekly frontal ice loss from seismic data Duration of seismic calving signals and catalog incompleteness mainly controlled by seismic noise level are suitable predictor variables Frontal ablation from Kronebreen reveals sharp summer increase, short‐lived effects of rainfall events, and characteristic decay in autumn